Influência de antibacterianos na morfofisiologia e susceptibilidade a antifúngicos de Cryptococcus gattii e Cryptococcus neoformans - Lívia Mara Vitorino da Silva (2023)
Cryptococcosis is an invasive mycosis that involves two main etiologic agents, Cryptococcus neoformans and C. gattii. The disease primarily affects the lungs, causing pneumonia, which can progress to meningoencephalitis. Amphotericin B and Fluconazole are the antifungals indicated for the treatment of this infection, however, an aggravating factor is that, many times, patients with cryptococcosis are also exposed to antibacterial agents, either for the empirical treatment of pneumonia and meningitis or for the treatment of coinfections bacterial. Therefore, the objective of this work was to evaluate the effect of antibacterials on the morphophysiology and susceptibility to antifungals of C. neoformans and C. gattii. For this, the following antibacterials were used: amoxicillin (AMO), amoxicillin + clavulanate (AMO + CLAV), ceftriaxone (CRO) and gentamicin (GEN). Initially, it was observed that antibacterials were not able to inhibit fungal growth, except for gentamicin, which exhibited MIC values between 32-256μg/ml. Next, we evaluated whether the combination of antibacterials could result in any interaction with clinical antifungals and whether exposure to antibacterials could interfere with antifungal susceptibility. It was observed that the combination of drugs resulted in an indifferent interaction and exposure to antibacterials was not able to select subpopulations of Cryptococcus less or more susceptible to antifungals. In addition, it was observed that AMO and CRO had a fungistatic effect on Cryptococcus and reduced the synthesis of melanin and polysaccharide capsule in the fungal cell. Gentamicin, in turn, showed a fungicidal effect associated with an increase in reactive oxygen species, a reduction in ergosterol content and melanin synthesis. Finally, we evaluated whether antibacterials could have any effect on the treatment of cryptococcosis in an infection model. However, despite the dynamic effect of antibacterials on Cryptococcus spp., treatment with these drugs alone or combined with amphotericin B was not sufficient to inhibit disease progression at the doses tested. This study brought unprecedented results on the in vitro effects of antibacterials on the morphophysiology and susceptibility to antifungals of Cryptococcus gattii and C. neoformans. Despite this evidence, we believe that new in vitro and in vivo assays are still needed for a better understanding of the effect of antibacterials in the context of cryptococcosis.